I interpret the question to mean derive the equation of the line with those two points:
y = mx +c
m is the gradient = (y1-y2)/(x1-x2) = (24-36)/(8-3) = -2.4
y = -2.4x + c
Substitute in one of the (x,y) pairs to find c:
24 = -2.4(8) + c => c = 24 + 19.2 = 43.2
y = 43.2 - 2.4x
well, your way seems to make sense, but i believe it was two different questions for the following reason:
By definition, we say x and y vary directly if:
x = ky
I have never seen a definition of direct variation, or varying directly that accounts for the possibility of a lone constant. that is,
x = ky + c is not direct variation by definition
and so i assumed it was two separate problems. plus, n_duncan2010 never said anything about me putting down two answers, so i guess it was really two problems